The genus philobrya j.G. Cooper, 1867 (bivalvia: philobryidae) in patagonia and adjacent antarctic waters - Urcola, Matías Ricardo; Zelaya, Diego Gabriel (Zootaxa)
The present study provides the first comprehensive revision of the species of Philobrya occurring in the Atlantic and Pacific coasts of Patagonia, the Strait of Magellan, the Beagle Channel, Isla de los Estados, Malvinas/Falkland Islands, Burdwood Bank, the Scotia Arc islands, the Antarctic Peninsula and the Bellingshausen Sea. Based on extensive collections, the identity of all species previously described from these areas is re-evaluated, and species are redescribed and figured, considering their ontogenetic variability. As part of this study, 15 taxa are recognized as valid, including Philobrya delli new species and another possibly new (Philobrya cf. barbata) species. Philobrya crispa Linse is considered a junior synonym of Philobrya blakeana (Melvill & Standen), and Philobrya antarctica (Philippi) is regarded as a nomen dubium. Neotypes for Philobrya sublaevis Pelseneer and Philobrya quadrata (Pfeffer) and a lectotype for Brachidontes (Hormomya) blakeanus are here designated. The clarification of the identity of P. sublaevis allows the revalidation of Philobrya limoides E.A. Smith and Philobrya orbiculata (Hedley), two species regarded as synonyms of P. sublaevis in the last 60 years. Furthermore, the synonymy of Philippiella Pfeffer, Stempelleria Clasing and Stempellia Odhner (non Léger and Hesse) with Philobrya is here confirmed. Fil: Urcola, Matías Ricardo. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología Experimental y Aplicada. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Biodiversidad y Biología Experimental y Aplicada; Argentina Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología ...